2011
DOI: 10.4081/hr.2011.e20
|View full text |Cite
|
Sign up to set email alerts
|

Total Remission of Severe Immune Thrombocytopenia after Short Term Treatment with Romiplostim

Abstract: Immune thrombocytopenia (ITP) in adults is an acquired chronic immune-mediated disorder defined by isolated thrombocytopenia. In recent years, an improved understanding of the pathophysiology of ITP has been achieved and it is now accepted that the disorder is due to increased platelet destruction and decreased platelet production from megakary-ocytes. Thrombopoietin (TPO)-receptor agonists (romiplostim and eltrombopag) are new therapeutic modalities in the treatment of ITP. Here we describe a case of an elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…A post hoc analysis [32] indicated that ITP duration ≤ 1 year could be a potential predictor for remission, although additional studies are needed to confirm this possibility. Similar results of sustained remissions after TPO-ra treatment and discontinuation have also been reported in several small case series of ITP patients [1820, 22, 27–29, 33]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A post hoc analysis [32] indicated that ITP duration ≤ 1 year could be a potential predictor for remission, although additional studies are needed to confirm this possibility. Similar results of sustained remissions after TPO-ra treatment and discontinuation have also been reported in several small case series of ITP patients [1820, 22, 27–29, 33]. …”
Section: Discussionsupporting
confidence: 86%
“…Several other reports had observed similar low doses in long-term remitters [1820, 22, 24, 30], being comparatively higher in patients not achieving stable platelets counts and subsequent discontinuation [24]. However, a direct causality between administered doses and remission status was not established.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of eltrombopag is transient, and platelet counts usually return to baseline within 2 weeks unless treatment is continued [8][9][10], but anecdotal evidence suggests that a number of patients have discontinued eltrombopag and been able to maintain platelet counts above baseline values without additional treatment [11,12]. This effect has been also reported with romiplostim [13][14][15][16][17][18]. Short-and medium-term treatment with TPO-RA may avoid side effects and reduce the financial burden this costly treatment places upon healthcare systems.…”
Section: Introductionmentioning
confidence: 94%
“…Despite the plethora of therapeutic strategies in ITP, there is no evidence to guide an algorithm of treatment for recurrent or persistent ITP cases [4]. Recently, thrombopoietin receptor agonists, namely romiplostim [5,24,25] and eltrombopag [6,10,11,12], have been established as novel second-line therapies in the treatment of chronic ITP.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an improved understanding of the pathophysiology of ITP has been achieved, consequently leading to new therapeutic options and strategies. It is now accepted that the disorder is due to both increased immune-mediated platelet destruction and decreased platelet production from megakaryocytes associated with endogenous thrombopoietin levels [3,4]. Therefore, thrombopoietin receptor agonists (romiplostim and eltrombopag) are new therapeutic modalities that have recently been licensed for the treatment of chronic ITP [5,6].…”
Section: Introductionmentioning
confidence: 99%